2010
DOI: 10.1111/j.1526-4610.2010.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Upper Cervical Facet Joint and Spinal Rami Blocks for the Treatment of Cervicogenic Headache

Abstract: C(1/2), C(2/3) facet joint injections and C(2), C(3) spinal rami blocks were effective and well tolerated for the treatment of cervicogenic headache in this study. The procedures provided significant and prolonged pain relief in the majority of patients. Larger controlled studies are needed to further evaluate the efficacy of this treatment modality in cervicogenic headache.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 14 publications
(16 reference statements)
1
28
0
Order By: Relevance
“…The C3 level may be effectively blocked reducing the pain stemming from the C2-C3 zygapophysial joint [84]. Again, facet joint injections (C1-C2 and C2-C3) and spinal rami blocks (C2 and C3) performed in 31 individuals with "refractory" CeH resulted in significant relief [80]. Despite favorable reports [85], a randomized, double-blind study designed to address the efficacy of botulinum toxin in CeH in 28 patients showed negative results.…”
Section: Treatmentmentioning
confidence: 95%
See 1 more Smart Citation
“…The C3 level may be effectively blocked reducing the pain stemming from the C2-C3 zygapophysial joint [84]. Again, facet joint injections (C1-C2 and C2-C3) and spinal rami blocks (C2 and C3) performed in 31 individuals with "refractory" CeH resulted in significant relief [80]. Despite favorable reports [85], a randomized, double-blind study designed to address the efficacy of botulinum toxin in CeH in 28 patients showed negative results.…”
Section: Treatmentmentioning
confidence: 95%
“…The greater occipital nerve anesthesia proved ineffective for the treatment of chronic migraine [78,79], and therefore, serves as a differentiating tool. As for CeH, the cervical C1-C2 and C2-C3 facet joint blocks, as well as C2 and C3 spinal rami (including the lesser and third occipital nerves) blocks induced prolonged pain relief in more than 90% of the patients [80]. The greater occipital nerve can be easily blocked and serves as important diagnostic evidence if a temporary relief is obtained [81,82].…”
Section: Treatmentmentioning
confidence: 98%
“…They concluded that these morphological changes were possibly the result of chronic vascular compression. In addition, several authors proposed that one of the most important structures involved in the pathogenesis of occipital headache is the lateral C1–C2 joint [131415]. Ehni and Benner [13] described a group of elderly patients suffering from an occipital neuralgic pain syndrome aggravated by neck motion due to degenerative changes in a C1–C2 arthrosis.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of the site for injection was determined by first having the patient identify the more painful side [8, 11]. An Esaote MyLab60 (Esaote, Italy) ultrasound machine equipped with a multifrequency linear probe (4–13 MHz) was used.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, several local anesthetic techniques have been used in treating CeH, including occipital nerve blocks, cervical facet joint blocks, and cervical epidural injections [8–11]. Real time fluoroscopy imaging guidance is frequently required to ensure correct needle placement [12–14].…”
Section: Introductionmentioning
confidence: 99%